The Use of Quiding Questions in Teaching Writing Procedure Text for Senior High Schools - Suci Noviarti; Aryuliva Adnan (Journal of English Language Teaching, 2019)
Writing is a process that allows students to elaborate their ideas and background knowledge creatively through written expression. In the 2013 curriculum, several text genres learned by Senior High School Students are divided into two parts. Those are functional text and monolog text. One of them is procedure text which belongs to a monologue text. However, there are some problems faced by students in writing procedure text. They are not able to organize their idea, do not understand the generic structure and language feature of the procedure text, not able to write an assignment and get distracted easily during writing task and the students also have other problems such as lack of vocabulary and find difficulty with sentence structure and word order. The other problems also come from the teacher itself. In order to help the students in writing a procedure text, the teachers should prepare a new method which creates the different learning style in the classroom. Moreover, the method given should be appropriate and effective for the students. In this case, guiding question technique is the appropriate applied in teaching writing procedure text. This technique presents the interesting way in the process of learning.